Increased bud load of the 'Cabernet Franc' grapevine influences the physical-chemical composition of the wine - Würz, Douglas André; Brighenti, Alberto Fontabella; Rufato, Leo (Revista de Ciências Agroveterinárias, 2024)
The objective of this work is to evaluate the effect of increased bud load on the physicochemical quality of wines made from 'Cabernet Franc' grapes grown in the highland region of Santa Catarina. The present work was treated during the 2016/2017 harvest, in a commercial vineyard, located in the municipality of São Joaquim. The treatments consisted of four levels of pruning: 15, 30, 50 and 75 buds plant-1. After six months of the elaboration process, the wine samples were obtained in triplicate regarding total acidity, reducing sugars, alcohol content, relative density, dry extract, ash, pH, glycerol, total polyphenol index (TPI), anthocyanins, color intensity and color tone. The increase in bud load results in wines with higher glycerol, total acidity, and pH contents. Loads of 30 and 50 buds plant-1resulted in higher ash and dry extract values. The increase in the bud load, above 50 buds plant-1, resulted in a reduction in the total polyphenol index of the wines. The highest values of color intensity and color tone were observed in loads of 30 and 50 buds plant.